A Rapid Numerical Method to Constrain 2D Focused Fluid Flow Rates Along Convergent Margins Using Dense BSR‐Based Temperature Field Data. Issue 7 (30th June 2021) - Kunath, Pascal; Chi, Wu‐Cheng; Berndt, Christian; Liu, Char‐Shine
Abstract: Estimates of the sub‐seabed fluid flow rates are important for understanding hydrological budgets, biogeochemical cycles, and physical properties of the sediments. Fluid flow rates and directions, however, are difficult to measure, particularly beneath the seafloor. We developed a rapid method to estimate regional fluid migration rates using an extensive database of seismic reflection profiles taken offshore SW Taiwan. We observe bottom‐simulating reflector (BSR) that deflects toward the seafloor near thrust faults that indicate localized heat flow variations. At these sites, advecting warm pore fluids transport heat to shallower depths and force the BSR shallower. Our 2D steady‐state numerical method quantifies the fluid flow rates required to cause such thermal anomalies. We found that fluid flow rates near the trench of the accretionary wedge range between 0.1 and 16 m 3 yr −1  m −1, with slower and faster rates generally associated with slope basin discontinuities and faults, respectively. To evaluate the fluid pattern evolution from subduction to collision, we studied three transects: one along the Manila subduction zone in the south and two in Taiwan's initial collision zone in the north. We quantified the fluid budget and partitioning of fluid flow between focused discharge through faults and diffusive flow through the wedge. Faults in Taiwan's accretionary wedge capture on average 25% of the total dewatering flux in the younger subduction zone and 38.5% in the tectonically mature collision zone. Our method provides estimates of fluid migration rates along convergent plate boundaries, and contributes to our understanding of focused fluid flow processes in many other regions. Plain Language Summary: Fluids play a key role in many subduction zone processes. However, quantitative constraints on flow expulsion rates and directions are limited. Efficient upward fluid migration through subbottom conduits can be generated tectonically, such as faults. Faults are ubiquitous along convergent margins; yet, a quantitative understanding of their impact on regional fluid budgets, flow rates, and distribution at vent sites remains unclear. We developed a rapid numerical method to constrain 2D focused fluid flow rates using seismically derived thermal structure and applied it to the subduction‐collision zone system off SW Taiwan. To study the influence of long‐term tectonic processes on the fluid budget, we remotely mapped the distribution and amount of focused fluid flow across the convergent margin, using a widespread shallow subbottom temperature field derived from a spatially dense seismic data set covering an area of more than 25, 000 km 2 . We combined the results with other previously published geophysical data sets to calculate the margin fluid budget. We found stronger fluid advection from depth along the collision zone, where thicker sediments are deformed more intensively. Our approach to quantify fluid fluxes is applicable to a range of tectonic regimes and can provide critical insight into local, regional, or even global fluid budget estimates. Key Points: Developed a method to quantify fluid flow rates from BSR‐based temperature data Identified fluid partitioning patterns off SW Taiwan from subduction to collision Focused fault‐related flow controls the local depth of the hydrate stability zone